PENGEMBANGAN SOAL TES HOTS BERBASIS KAHOOT PADA MATERI PERALATAN DAPUR UNTUK SISWA SMK KULINER FASE E - Wanda Putri Dwi Wardani; Sri Handajani (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This research is motivated by the low level of Higher Order Thinking Skills (HOTS) among Culinary Vocational High School students. The daily learning evaluation process is still dominated by Lower Order Thinking Skills (LOTS) questions and the limited use of interactive digital media in assessments. This study aims to determine the development results and feasibility of a HOTS test instrument based on the Kahoot game-based learning platform for kitchen equipment for Phase E Culinary Vocational High School students. The research method used is Research and Development (R&D), referring to the 4D development model (Define, Design, Develop, Disseminate). However, due to time and scope constraints, this study was limited to the Development stage. The research location was SMKN 2 Jombang, with a limited trial population of 66 11th-grade Culinary students. The results of the study showed that: (1) The results of the material validation obtained an average percentage of 88% (very valid), the construction aspect was 88% (very valid), and the language aspect was 89% (very valid). The validation of the Kahoot media was in the very feasible category with the achievement of the display aspect of 91%, ease of use of 91%, and timeliness of 88%. (2) The results of the empirical trial analysis of 30 multiple choice questions developed resulted in 23 questions being declared valid and 7 questions being invalid. The reliability test of the valid questions obtained a Cronbach's Alpha coefficient of 0.80 which is included in the very high category. In terms of discrimination power, there were 2 questions in the good category and 21 questions in the very good category. The analysis of the level of difficulty resulted in 4 questions in the difficult category, 10 questions in the medium category and 9 questions in the easy category. The distractor function analysis showed 8 questions in the sufficient category, 8 questions in the good category, and 7 questions in the very good category. Based on these results, the developed Kahoot-based HOTS test questions were deemed highly suitable and reliable for use as an evaluation instrument for culinary learning.